First Record and Molecular Confirmation of the Brown Mussel Perna perna (Linnaeus, 1758) in the Aegean Sea, Turkiye - Ugur, Sinem; Yokes, Mehmet Baki; Yigitkurt, Selcuk; Yildirim, Sukru; Durmaz, Yasar (Springer Int Publ Ag, 2026)
This article reports the evidence of the bioinvasion of the widely invasive mytilid mussel Perna perna (Linnaeus, 1758) on the Turkiye coast. A freshly dead shell and a live specimen of P. perna were collected for the first time from the Tuzla site in Izmir Bay, Turkiye. During the commercial harvest of Mediterranean mussels (Mytilus galloprovincialis) at a mussel farm off the coast of Tuzla, Izmir, in March and August 2024, the brown mussel P. perna was found at a depth of 8 m. The freshly dead shell, discovered in March, measured 115.08 mm in length, while the live specimen, recorded in August, had a shell length of 102.83 mm. Additionally, the genetic analysis of 607 base pairs revealed a 100% match with P. perna sequences in both the NCBI BLAST search and the Barcode ID search on the BOLD platform. This article also provides an overview of current P. perna records in the Mediterranean Sea, including recent findings from the Aegean coast of Turkiye.
Keywords: Perna Perna; Brown Mussel; First Record; The Aegean Sea; T & Uuml;Rkiye